Students' Attitudes toward Problem Based Learning – Analog Electronic Course in the Electrical Engineering Programs in PPU Case Study - Arman, Abdallah (IBIMA Publishing, 2018)
In Palestine, there is a growing recognition for innovative teaching and learning approaches such as Problem-Based Learning (PBL) in engineering education in order to develop competence graduates. According to Kitogo (2011), “today’s graduates have attractive curricula vitae, but practically, their performance is insufficient; it doesn’t match with what they claim to have studied”. The researcher sees that people learn when being actively involved in constructing meaning. In other terms, successful learning requires individuals' active participation and involvement. PBL as a dynamic approach of teaching in which students explore real-world problems, issues and challenges, students are inspired to obtain a deeper knowledge of the subjects they are studying and more likely to retain the knowledge gained through this approach far more readily than through traditional textbook centered. This principle agrees with the Chinese saying "Tell me and I forget, show me and I remember, involve me and I learn".This article presents a survey about the usage and the attitudes toward education technology at PPU in Palestine. The survey aims at assessing the experience, skills and computer efficacy of students, measuring their attitudes towards the use of education technology and distinguishing obstacles for the development of a co- operative learning environment. The results indicate positive attitudes of students toward this new approach of learning. The survey is used for the development of the university teaching and learning strategies, providing information on how to establish systems and procedures that enable the effective use of a PBL approach.
Keywords: Project Based Learning, Features, Analog Electronics, Students’ Attitude